(untitled) (Journal of Dhaka National Medical College & Hospital, 2015)
Objective : The main objective of this study was proper detection of the compromised fetus to allow for timely intervention and to reduce perinatal morbidity and mortality. Materials and Methods This is a cross sectional descriptive type of study which was conducted in the department of Obstetrics and Gynaecology in DNMCH from January 2006 to December 2006. Results : In this study gestational age was determined by clinical examination, LMP and USG. There was a high incidence of caesarean section in this study. The reason of this high incidence was due to obstetrics indications like severe preeclampsia, severe PIH, Oligohydramnios, indications of emergency caesarean section was (58.97%). High risk cases were decided to terminate by Umbillical artery Doppler study. In the present study in most cases delivery occurs within 3-4 days of the last test. The prevalence of perinatal death in fetuses with absent or reversed end diastolic flow velocity was 40%. 5 minute Apgar score<7 was 8% and admission into NICU was 32%. Timely intervention dictated by Umbilical Artery Doppler Study results may be the reason for such variation. Conclusion : UADS as an antepartum surveillance technique is highly sensitive, non-invasive, convenient technique, less time consuming to perform it and from legal point there is a record. UADS may be used as supplementary test which may improve perinatal outcome. Hence the use of Doppler provides information that is not readily obtained from more conventional test of fetal well being. It is therefore has an important role to play in the management of compromised fetus. J. Dhaka National Med. Coll. Hos. 2015; 21 (01):19-22